GATA-4 upregulates glucose-dependent insulinotropic polypeptide expression in cells of pancreatic and intestinal lineage - Jepeal, Lisa I. (2008)
A thorough examination of glucose-dependent insulinotropic polypeptide (GIP) expression has been hampered by difficulty in isolating widely dispersed, GIP-producing enteroendocrine K-cells. To elucidate the molecular mechanisms governing the regulation of GIP expression, 14 intestinal and pancreatic cell lines were assessed for their suitability for studies examining GIP expression. Both STC-1 cells and the pancreatic cell line βTC-3 were found to express GIP mRNA and secrete biologically active GIP. However, levels of GIP mRNA and bioactive peptide and the activity of transfected GIP reporter constructs were significantly lower in βTC-3 than STC-1 cells. When βTC-3 cells were analyzed for transcription factors known to be important for GIP expression, PDX-1 and ISL-1, but not GATA-4, were detected. Double staining for GIP-1 and GATA-4 in mouse duodenum demonstrated GATA-4 expression in intestinal K-cells. Exogenous expression of GATA-4 in βTC-3 cells led to marked increases in both GIP transcription and secretion. Lastly suppression of GATA-4 via RNA interference, in GTC-1 cells, a subpopulation of STC-1 cells with high endogenous GIP expression resulted in a marked an attenuation of GIP promoter activity. Our data support the hypothesis that GATA-4 may function to augment or enhance GIP expression rather than act as an initiator of GIP transcription.